E-SERVICE QUALITY DARI MOBILE APPLICATION KAI ACCESS PT KERETA API INDONESIA (PERSERO) DAOP II BANDUNG - Devina Sri Rahayu (Journal of Applied Business Administration, 2022)
The growth in the number of internet users in Indonesia continues to increase, PT Kereta Api Indonesia (Persero) takes advantage of this by releasing KAI Access to improve service quality and also as an anticipation in reducing the number of queues at train station counters. However, after being introduced, the application obtained a 3.4/5 rating from KAI Access users, prompting PT KAI to enhance e-service quality on KAI Access. The degree of service delivered to consumers over the internet is referred to as e-service quality. In this study, the Importance Performance Analysis (IPA) technique is utilized to examine the link between KAI Access application expectations and performance. This study uses a quantitative descriptive approach. Overall, the expected value of e-service quality in the KAI Access application is in the important category with a percentage of 82 percent, while the performance value of e-service quality in the KAI Access application is in the good category with a percentage of 72 percent, according to the results of descriptive analysis. Based on the results of the Importance Performance Analysis (IPA), PT KAI can divide the strategy formulation into four parts by paying attention to the main priority aspects (Quadrant I), which has six statement items, then the aspects that should be maintained in its performance (Quadrant II), which has sixteen statement items. The low priority aspect (Quadrant III) has five statement items, and the aspect that is considered excessive (Quadrant IV) has six statement items. According to the findings of this study, KAI Access must improve system performance in the program being run so that loading, error/freeze, or force closes do not occur when KAI Access users use it. Keywords: e-service quality, importance performance analysis, KAI Access